Analysis on Various Strategies of Partitioning Between India and Pakistan: Examining the Determinants of Ethnic Cleansing during the Partition of India (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The partition of ethnically-diverse regions intohomogeneous `homelands' has been often mooted as a solution to civil war andethnic convict. However, the Partition of India in 1947, in which an estimated3.4 million people went missing, looms large as a cautionary example. Yet,despite its iconic importance, systematic evidence assessing the political andeconomic determinants of ethnic cleansing during the Partition has hithertobeen lacking. Using novel data, this study assesses the determinants ofminority outwards from Indian districts between 1931 and 1951 and documentsthat districts that raised army units that were arbitrarily assigned toexperience longer combat experience in